The Development of Inquiry-Based LKPD to Enhance Critical Thinking Skills in Science learning at Elementary Schools - Sisri Wahyuni; Yeni Nurpatri; Festiyed; Yerimadesi; Heffi Alberida; Yuni Ahda (Postgraduate, University of Mataram, 2025)
This research is motivated by the development of LKPD (Student Worksheet) for enhancing critical thinking skills of elementary school students. The LKPD used has not yet captured the students' attention. The LKPD has not been able to improve students' learning motivation because it does not align with their learning styles. LKPD serves as teaching material used by teachers to facilitate the delivery of content and achieve learning objectives. This study aims to develop LKPD and assess its validity using the Inquiry model to improve critical thinking skills in Science education about the conservation of natural resources in the 4th-grade class. The type of research used is research and development (R&D), employing the 4-D model. This model consists of four development stages: define, design, development, and dissemination. Based on the results of the validation of LKPD using the Inquiry model to enhance critical thinking skills, the LKPD is deemed feasible for use. The material aspect validation result was 85.41% (valid), the design aspect validation result was 86.53% (valid), and the language aspect validation result was 94.44% (very valid). Therefore, the LKPD using the Inquiry model to improve critical thinking skills is valid.